College students' communication about complementary and alternative medicine practices - Heather J. Carmack; Julie A. Serafin (Qualitative Research in Medicine & Healthcare, 2018)
While the use of Complementary/Alternative Medicine (CAM) has increased over the last two decades, how patients communicate about their decisions to use CAM has yet to be fully explored. The purpose of this study is to examine college students’ decision-making and communication about CAM. Fourteen college students participated in semi-structured focus group interviews about their CAM use and communication about CAM with family, friends, and health care providers. Participants use CAM to improve their physical and mental health. However, they have difficulties justifying their decision to practice CAM to others. They relied on CAM not only for physical and mental stability, but also as a sounding board for larger spiritual issues. Participants use passive communication strategies to communicate about their CAM use and often do not disclose CAM use to their providers because of the stigmas related to CAM. There is potential danger for CAM users who do not disclose CAM use to providers, family, and friends. More efforts are needed to encourage open and honest communication about CAM use.